ANALISIS PENDAPATAN RUMAH TANGGA USAHATANI CENGKEH DI DESA SALUMPAGA KECAMATAN TOLITOLI UTARA KABUPATEN TOLITOLI - Rafika, Ika (Katalogis, 2015)
This study aims to determine the effect of capital, labor and the cost of the clove farm household income. The research method of survey is used and the sample is notified by simple random. The results shows that the independent variables which are include capital, labor, expense, have simultaneous affect on the clove farm income (Y) in Salumpaga village, North Tolitoli Sub-district-Tolitoli Regency. Meanwhile, the capital variable (X1) has partial positive relationship on the clove farm household income (Y). The labor variables (X2) has negative effect ans significant on the clove farm household revenue (Y). Following that, the cost variable (X3) has negative and significant effect on the clove farm household income (Y). The land area variable (X4) has positive and significant impact on the clove farm household income (Y). The farming experience variable (X5) has positive and significant impact on the clove farm household revenueÂ (Y). The number of trees variable (X6) has positive and significant impact on the clove farm house hold income (Y). In addition, the education variable (D1) has positive and significant impact on the clove farm household income (Y) in the village of Salumpaga,Â North Tolitoli sub district- Tolitoli Regency. Furthermore, this study found that the average of the clove farm household income in the village of Salumpaga is more than Rp 1.000.000-.Therefore, the comparison between the revenue and expenditure of the clove farm in the village of Salumpaga, North Tolitoli sub district is feasible to be developed.